PENGEMBANGAN PEMBELAJARAN MODEL INDUKTIF DALAM UPAYA MENINGKATKAN KEMAMPUAN MENGAPRESIASI PUISI PADA SISWA SMP NEGERI DI KABUPATEN SIDOARJO - ., Warsiman (Inovasi: Jurnal Diklat Keagamaan, 2016)
The objective of this research is to improve students’ ability inappreciating poetry through inductive model. Method of researchthat is used is Research and Development which is modified. Dataanalysis technique that is used is descriptive analysis. The result ofresearch shows that learning through inductive model that concernthose eight instructional steps can improve students’ ability inappreciating poetry. The improvement can be seen numericallyfrom the average of evaluation result and observation in everytreatment. I n the fi rst i mplementati on, the average score ofevaluation result was 60.9, in the second implementation was 62.4and in the third implementation was 65.3, while the average score ofresult in the implementation I from ’less’ criteria gradually become’enough’ criteria, in the implementation II from ’enough’ criteriagradually become ’good’ criteria an in the implementation III from’good’ criteria gradually become ’very good’ criteria.